A Facially Coordinating Tris‐Benzimidazole Ligand for Nonheme Iron Enzyme Models. Issue 7 (14th January 2021) - Gunasekera, Parami S.; Abhyankar, Preshit C.; MacMillan, Samantha N.; Lacy, David C.
Abstract: Herein, we report a new tripodal tris‐benzimidazole ligand (Tbim ) that structurally mimics the 3‐His coordination environment of certain nonheme mononuclear iron oxygenases. The coordination chemistry of Tbim was explored with iron(II) revealing a diverse set of coordination modes. The aerobic oxidation of biomimetic model substrate diethyl‐2‐phenylmalonate was studied using the Tbim −Fe and Fe(OTf)2 . Abstract : A new tripodal tris‐benzimidazole ligand (Tbim ) that structurally mimics the 3‐His coordination environment of nonheme mononuclear iron oxygenases was prepared and coordinated to iron and revealed diverse coordination chemistry. The aerobic oxidation of biomimetic model substrate diethyl‐2‐phenylmalonate was studied using the Tbim −Fe and Fe(OTf)2 .